2016
DOI: 10.1186/s13018-016-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

The importance of reaming the posterior femoral cortex before inserting lengthening nails and calculation of the amount of reaming

Abstract: BackgroundLengthening nails have been used to correct limb length discrepancy caused by different etiologies, as well as for post-traumatic reasons. Two important lengthening nail-related complications are damage to the distraction mechanism and femoral fractures around the nail tip. As a result of the curved anatomy of the femur, straight nails impinge on the anterior cortex. Therefore, proper reshaping of the medullary canal to accommodate straight lengthening nails is crucial for the prevention of this prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…The effect of lengthening the femur along the anatomic axis is to lateralize the mechanical axis [ 23 ], but this seemed to have no radiographic or clinical impact on outcome due to the modest amount of lengthening done in these cases. The BHI was low (24 days/cm), which was in keeping with observations from multiple studies on the ILN in femur reconstruction [ 21 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The effect of lengthening the femur along the anatomic axis is to lateralize the mechanical axis [ 23 ], but this seemed to have no radiographic or clinical impact on outcome due to the modest amount of lengthening done in these cases. The BHI was low (24 days/cm), which was in keeping with observations from multiple studies on the ILN in femur reconstruction [ 21 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…Few studies on retrograde ILN have documented the distance of the distal femoral osteotomy to the intercondylar notch. One study reported an average distance of 81 mm [ 24 ]. Krieg et al [ 25 ] explain that a limitation of retrograde ILN surgery is the need for a distance of 70–110 mm from the joint line to the osteotomy site, the variation being due to differences in femur length between patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 1 (IL-1) regulates immune reaction and inflammation [1,3,14], and expression of IL-1 in a variety of tissue factors is promoted by the synthesis of IL-2, IL-6, and IL-8 related cytokines. Expression of IL-1 in wet arthritis induces cartilage cells surrounding matrix degradation, resulting in cartilage cell apoptosis [18]. In the present study of the process of lumbar disc herniation, the mechanism of cartilage cells apoptosis was found to be the most important process.…”
Section: Discussionmentioning
confidence: 61%
“…20-24 One case report was excluded, one that did not meet the definition of CKD, 25 and another because it was a narrative review. 26 Finally, only 3 articles met the eligibility criteria and were included in this review.…”
Section: Resultsmentioning
confidence: 99%